Service Business Costing Cost Accounting Approach for the Service Industry - Baum, Markus B. (Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2013)
Service firms have high overhead costs which are difficult to assign to individual services. To bring transparency to their value chain, they need costing approaches that help them find their own improvements. Markus B. Baum explores current theory and practice of value chain approaches and cost accounting to develop a costing approach with a suitable instrument for the allocation of fixed and overhead costs for a service firm. He describes the service business costing (SBC) approach. This hybrid-costing model has a hierarchical structure in terms of consolidation and allocates cost and revenues on the lowest hierarchical level possible to ensure that all costs and income are assigned to activities from which they originated.